Comprehensive Review of Healthcare System Challenges, Resource Distribution, and Patient Safety - Alqaysi, Halima Ali Ahmed; Al- Sarar, Mohammed Masoud Hassan; Alhetela, Nawal Mohammed Mohammed; Alsallum, Mashan Ali Mohammed; Alyami, Mutyi Saleh Hadi; Alsuliman, Alhassan Rajeh Mohamed; Alsuliman, Salem Rajeh Mohamed; Almtyif, Ali Yahya Hamad; Al Sharyah, Ali Hamad; Alshokhah, Namah Abdullah Husain; Almatlag, Saeed Abdalaziz Sahl (Journal of Ecohumanism, 2024)
Healthcare systems all around the globe are experiencing a plethora of problems, namely ineffective operation of the supply chain, unfair division of access to important healthcare services, and questions about patients’ security. These challenges differ from country to country depending on the current healthcare model, resources, and infrastructure available. This review will determine what has made the healthcare system inefficient and what role resource distribution has in patient safety. Based on the available literature review and research studies, this paper analyzes the various healthcare systems to understand how resources are managed and which strategies can best optimize patient safety. It gives an understanding of the issues that health facilities have when it comes to issues of fairness, availability, and quality.